THE IMPORTANCE OF COLLOIDS FOR THE BEHAVIOR OF URANIUM ISOTOPES IN THE LOW-SALINITY ZONE OF A STABLE ESTUARY - Andersson P.S.; Porcelli D.; Gustafsson O.; Ingri J.; Wasserburg G.J. (My University, 2001)
Particle-mediated removal processes of U isotopes were investigated during spring flood discharge in the low-salinity zone (LSZ, up to 3 practical salinity units [psu]) of a stable estuary. A shipboard ultrafiltration cross-flow filtration (CFF) technique was used to separate particles (>0.2 μm) and colloids (between 3000 daltons (3 kD) and 0.2 μm) from ultrafiltered water (<3 kd) containing ''dissolved'' species. sediment traps were used to collect sinking material. concentration of fe and organic c, which are indicators the major u carrier phases, interpret behavior 234U-238U during estuarine mixing.Colloids dominated the river water transport of U, carrying ~90% of the U. On entering the estuary, colloids accounted for the dominant fraction of U to about a salinity of 1 psu, but only a minor fraction (<5%) at 3 psu. A substantial fraction of the total U is removed at <1 psu by fe-organic rich colloids that aggregate and sink during initial estuarine mixing in the kalix river estuary. contrast, at salinities>1 psu, there is a general correlation between U and salinity in all filtered fractions. The 234U/238U ratios in different filtered fractions and sinking particles were generally indistinguishable at each station and showed enrichment in 234U, compared with secular equilibrium (δ234U = 266-567). This clearly shows that all size fractions are dominated by nondetrital U. Consideration of U isotope systematics across the estuary reveals that substantial U exchange must occur involving larger particles at least to 1 psu and involving colloids at least to ~1.5 psu. Further exchange at higher salinities may also occur, as the proportion of U on colloids decreases with increasing salinity. This may be due to decreasing colloid concentration and increasing stabilization of uranyl carbonate complexes during mixing in the estuary.The results show that although U is a soluble element that shows generally conservative mixing in estuaries, removal occurs in the very low salinity zone, and this zone represents a significant sink of U. Variation in composition and concentration of colloidal particles between different estuaries might thus be an important factor for determining the varying behavior of U between estuaries.